Emulsions, dipsticks and membranes based on oxalic acid-treated nanocellulose for the detection of aqueous and gaseous HgCl2 - Bastida, Gabriela Adriana (2024)
Although cellulosic materials have been used as stabilizing agents for oil-in-water emulsions since the 1980s, their properties and the underlying mechanism are not universal regardless of the dispersed phase or of the treatments on cellulose. One case of unconventional organic phase is acetic acidcontaining chloroform, which is known to be a good solvent system for the preservation of dithizone. In turn, dithizone is a long-known chromogenic reagent for the colorimetric detection of HgCl2. However, its usefulness is limited by its fast degradation in polar solvents. For instance, its dissolution in ethanol and the subsequent impregnation of paper strips allowed to quantify aqueous HgCl2 reliably and quickly (5.4 – 27 mg L–1), but only if they were used along the first 24 h after dip coating. Furthermore, those strips could not be used for sublimated HgCl2. The dithizone/chloroform-in-water emulsions presented in this work overcame these limitations. We opted for oxalic acid-treated cellulose nanofibers (ox-CNFs) as stabilizer, aiming at a proper balance between amphiphilic character and electrostatic repulsion. In this sense, ox-CNFs attained good gel-forming ability with a low content of carboxylate groups. The minimum ox-CNF concentration required was 0.35 wt%, regardless of the proportion of chloroform. This consistency implied yield stress values above 0.7 Pa. Nanocellulose also provided film-forming capabilities, which were exploited to produce visually responsive dipsticks and membranes. While quantification and reproducibility were hampered by the increase in the complexity of the system, dithizone/ox-CNF films were still a valid option for HgCl2 detection, outperforming solution coating in terms of stability, blank signal, and selectivity.